2015
DOI: 10.1093/hmg/ddv318
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the role of the A2Aadenosine receptor in neurodegeneration using neurons derived from Huntington's disease iPSCs

Abstract: Huntington's disease (HD) is an autosomal-dominant degenerative disease caused by a cytosine-adenine-guanine trinucleotide expansion in the Huntingtin (htt) gene. The most vulnerable brain areas to mutant HTT-evoked toxicity are the striatum and cortex. In spite of the extensive efforts that have been devoted to the characterization of HD pathogenesis, no disease-modifying therapy for HD is currently available. The A2A adenosine receptor (A2AR) is widely distributed in the brain, with the highest level observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 65 publications
1
76
0
3
Order By: Relevance
“…We previously reported that HD-iPSC-derived neurons are vulnerable to DNA damage, and that stimulation of A 2A R using selective agonists reduced DNA damage in HD-iPSC-derived neurons (Chiu et al., 2015). To identify whether the HD-iENPs and their neuronal derivatives recapitulate the above features of HD, we treated HD-iENPs and control-iENPs with a selective A 2A R agonist, CGS21680.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that HD-iPSC-derived neurons are vulnerable to DNA damage, and that stimulation of A 2A R using selective agonists reduced DNA damage in HD-iPSC-derived neurons (Chiu et al., 2015). To identify whether the HD-iENPs and their neuronal derivatives recapitulate the above features of HD, we treated HD-iENPs and control-iENPs with a selective A 2A R agonist, CGS21680.…”
Section: Resultsmentioning
confidence: 99%
“…Several lines of evidence have indicated that stress factors can cause DNA damage and increase profound neuronal death in cells derived from HD patients (Jackson and Bartek, 2009). Also, it has been reported that A 2A R agonists are beneficial in HD transgenic animal models and an HD-iPSC-derived neuronal population (Chiu et al., 2015). In line with these observations, our results demonstrated that HD-iENPs and their neuronal derivatives were more susceptible to DNA damage than their counterparts derived from normal FBs.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the tumor necrosis factor-alpha (TNF α ) inhibitor XPro-1595 decreased cytokine induced apoptosis in neurons derived from iPSCs with 43 CAGs [89]. Adenosine receptor 2A agonists CGS-21680 and APEC reduced oxidative stress toxicity in the cells exposed to H 2 O 2 by decreased γ -H2A Histone Family Member X ( γ H2AX) induction and caspase 3 cleavage [90]. …”
Section: Ipscs Providing New Tools For Developing Treatments For Cmentioning
confidence: 99%
“…These examples represent endpoints suitable for HD screens in a high throughput format, which is especially valuable when screening thousands of potential therapeutic candidates. Other phenotypes that have been identified in MSNs derived from human HD-iPSCs are increased expression of γH2AX and elevated oxidative stress (67). In this study the A 2A R-selective agonists protected MSNs through the cAMP/PKA-dependent pathway (67).…”
Section: Phenoytpes In Human Derived Hd-ipscs Cells Typesmentioning
confidence: 99%
“…Other phenotypes that have been identified in MSNs derived from human HD-iPSCs are increased expression of γH2AX and elevated oxidative stress (67). In this study the A 2A R-selective agonists protected MSNs through the cAMP/PKA-dependent pathway (67). Also observed in human HD NSCs is a deficit is manganese-dependent activation of p53 (68).…”
Section: Phenoytpes In Human Derived Hd-ipscs Cells Typesmentioning
confidence: 99%